PENGARUH GAYA HIDUP TERHADAP PERILAKU PEMBELIAN KONSUMEN KOSMETIK AVON DI SURAKARTA - Paningrum, Destina (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2012)
Background: Cosmetic is one of needs that is always used by thewomen. Now, it will beÂ anÂ importantÂ thingÂ firÂ everyÂ woman,Â oneÂ ofÂ theÂ mostÂ famousÂ cosmeticÂ isÂ Avon.Â Avon must be able to satisfied the consumerâs needs, andone of them is the influence of lifestyle that growth in each dimension, such as the activity, opinion, and interest. The Research Purpose: This research is aimed to know how a lifestyle thatgrows in the activity, opinion, and interest dimension and what kinds of dimension that is influential to the Avonâs consumers ResearchÂ Method:Â TypeÂ ofÂ thisÂ researchÂ isÂ surveyÂ research,Â whereÂ the sample derivationÂ isÂ doneÂ purposivelyÂ withÂ ClassifiedÂ SimpleÂ RandomÂ SamplingÂ MethodÂ around SurakartaÂ areas,Â usingÂ 5Â counters,Â byÂ 100Â respondentsÂ andÂ thenÂ itÂ isÂ analizedÂ byÂ double regression, discriminant, F test, and t test. ResearchÂ finding: (1)Â ActivityÂ ofÂ dimensionÂ lifestyleÂ isÂ influential positivelyÂ and significantlyÂ onÂ cosmeticÂ buying-seenÂ fromÂ sellingÂ intensity.Â (2)Â ActivityÂ andÂ opinionÂ of dimension lifestyles are influential positively andsignificantly on cosmetic buying-seen from theÂ numberÂ ofÂ product.Â (3)Â ActivityÂ andÂ interestÂ of dimensionÂ lifestylesÂ areÂ influential positively and significantly on cosmetic buying-seen from the kinds of product. (4) Activity of dimension lifestyles is the most influential lifestyle dimension-seen from selling intensity, number of product, and the kinds of product.